The effect of acupressure on pain, menstrual symptoms, and comfort in adolescents with primary dysmenorrhea: a single-blind randomized controlled trial - Ahu Aksoy-Can; Aysu Buldum; Arzu Abiç; Duygu Vefikuluçay-Yilmaz (BMC Complementary Medicine and Therapies)
Abstract Background Integrative therapies, such as acupressure, may be employed for the management of primary dysmenorrhea (PD), which is a prevalent condition with a particularly high prevalence among adolescents. Aim This study was conducted as a single-blind randomized controlled trial to determine the effect of acupressure on pain, menstrual symptoms, and comfort in adolescents with PD. Design A two-arm randomized controlled trial. Methods A total of 56 female adolescent students were randomly assigned to either the acupressure group (n = 28) or the sham group (n = 28) using block randomization. The acupressure group applied self-acupressure to the LI4, ST36, and SP6 points, while the sham group applied self-sham acupressure to points 1.5 cm around the same points for a period of three menstrual cycles (12 weeks) for an average of 15 min, immediately after waking up and just before going to bed on the first three days of menstruation. The primary outcome was Visual Analog Scale (VAS), and the secondary outcome were Menstruation Symptom Questionnaire (MSQ) and the General Comfort Questionnaire (GCQ). Results A comparison of the acupressure group with the sham group revealed a statistically significant decline in VAS and MSQ scores, while GCQ scores demonstrated a notable increase at the end of the 12-week study period (p < 0.05). An intragroup comparison revealed a statistically significant decrease in the VAS scores of the acupressure group over time (p < 0.001). For both groups, there was a decrease in the MSQ scores and an increase in the scores obtained from the socio-cultural domain subscale of the GCQ over time (p < 0.05). Conclusion The results demonstrated that acupressure is an efficacious approach for alleviating pain and menstrual symptoms, as well as enhancing comfort. Consequently, regular acupressure may be a viable option for the management of PD in young women. Trial registration This randomized controlled trial was conducted in accordance with the Consolidated Standards of Reporting Trials (CONSORT) guidelines and registered with ClinicalTrials.gov (NCT05408611) on dated 01.06.2022.